2022
DOI: 10.5194/esurf-10-1233-2022
|View full text |Cite
|
Sign up to set email alerts
|

Combining seismic signal dynamic inversion and numerical modeling improves landslide process reconstruction

Abstract: Abstract. Landslides present a significant hazard for humans, but continuous landslide monitoring is not yet possible due to their unpredictability. In recent years, numerical simulation and seismic inversion methods have been used to provide valuable data for understanding the entire process of landslide movement. However, each method has shortcomings. Dynamic inversion based on long-period seismic signals gives the force–time history of a landslide using an empirical Green's function but lacks detailed flowi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…The results of laboratory model testing showed that when the fine particle content reached about 28%, the slag debris flow can occur under weak climatic-hydrological conditions [17]; it was also observed in a similar model that the collapse of an accumulation body made it easy to produce slide-blockage-collapse-type debris flows at this level of fine particle content, and required the minimum amount of water [7,18]. The process of particle migration and deposition was established using a numerical model, and the instability failure and possible harm of the accumulation body were analyzed and calculated [19][20][21][22][23]. In order to determine the influence mechanism of fine particle migration, deposition and clogging more effectively on the instability of the accumulation slope, Wang et al [24], through the method of model testing, found that fine particles would migrate with rainwater, block the fine pores and reduce the permeability of soil, eventually leading to failure or collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The results of laboratory model testing showed that when the fine particle content reached about 28%, the slag debris flow can occur under weak climatic-hydrological conditions [17]; it was also observed in a similar model that the collapse of an accumulation body made it easy to produce slide-blockage-collapse-type debris flows at this level of fine particle content, and required the minimum amount of water [7,18]. The process of particle migration and deposition was established using a numerical model, and the instability failure and possible harm of the accumulation body were analyzed and calculated [19][20][21][22][23]. In order to determine the influence mechanism of fine particle migration, deposition and clogging more effectively on the instability of the accumulation slope, Wang et al [24], through the method of model testing, found that fine particles would migrate with rainwater, block the fine pores and reduce the permeability of soil, eventually leading to failure or collapse.…”
Section: Introductionmentioning
confidence: 99%
“…The geological environment is fragile due to steep terrain, substantial river incision, active tectonic activity, weak lithology, and frequent earthquakes (Zhang et al, 2000;Zhang et al, 2016). These internal and external dynamics of geological processes provide favourable conditions for the occurrence of geological hazards, especially landslides (Li et al, 2019;Ling et al, 2021;Zhao et al, 2019;Yan et al, 2022). Landslides are the most critical type of geological disaster and have the characteristics of a wide distribution area, high frequency of occurrence, fast movement speed, and severe losses.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2022) also proposed a dynamic prediction method of landslide displacement. However, the discrete element method can consider the dynamic process of sliding in the simulation process, and has achieved good results in the simulation of several typical landslide cases (An et al 2020;Xia et al 2021;Yan, Cui, et al 2022). The landslide risk division method based on the calculation results of landslide movement processes has also been studied (An et al 2020).…”
Section: Introductionmentioning
confidence: 99%